Rancang Bangun Sistem Informasi Penggajian Guru Berbasis Website di Smas Plus Guna Cipta Cimanggung - Nur Fatwa, Shinta; Pirous, Haekal (Jurnal Dimamu, 2024)
Design of Teacher Payroll Information System is a system created to solve problems in the financial department, especially the payroll of teachers and staff at SMAS Plus Guna Cipta Cimanggung. The existence of a system that runs by recording payroll transactions and calculations still using semi-computerization, making it vulnerable to calculation errors and data redundancies. Data that is still separate causes the payroll process to take longer. As well as the difficulty of making payroll reports and pay slips because they have not been automatically computerized. The purpose of this research is to facilitate teachers or officers concerned in managing teacher payroll. And all users can access this information system more flexibly anywhere and anytime. The research method used is the Object Oriented Analysis and Design (OOAD) system with its development model, namely the Rational Unified Process (RUP) and its system design using the Unified Modeling Language (UML The results of the study show that this system can facilitate the process of managing teacher salaries more precisely and efficiently with easy access anywhere and anytime. Moreover, this system has a feature to manage attendance data using QR Codes.